PID Controller-Based Simulations for Controlling Inverter Voltage to Enhance Power in a Microgrid - Maulidin, Reza; Nugroho, Bayu Rahmad; Kusmantoro, Adhi (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2025)
An inverter is a device that converts direct current (DC) into alternating current (AC), which is crucial in various applications, including solar power systems, uninterruptible power supplies (UPS), and electric motor control. Accurate and stable voltage control of the inverter is essential to ensure the performance and reliability of the system. The Proportional-Integral-Derivative (PID) control method is one of the most commonly used control techniques due to its simplicity and effectiveness across different control systems. This study focuses on the implementation of inverter voltage control using a PID controller. The PID controller is designed to regulate the inverter's output voltage, ensuring stability even in the presence of disturbances or load variations. In this research, the mathematical model of the inverter and the PID control system is developed and simulated using MATLAB/Simulink software. The simulation results demonstrate that the PID controller effectively maintains the inverter's output voltage, providing a rapid transient response with minimal overshoot. The application of the PID controller to the inverter also shows improvements in system stability and a reduction in steady-state error. Furthermore, precise tuning of the PID parameters is a key factor in achieving optimal control performance. This research makes a significant contribution to the field of inverter control by demonstrating the effectiveness of the PID controller in regulating the inverter's output voltage. The practical implementation of PID controllers on inverters is expected to enhance the efficiency and reliability of power systems that utilize inverters.